PENGARUH PEMBERIAN KONSELING OBAT TERHADAP KEPATUHAN PENGGUNAAN OBAT TUBERKULOSIS DI PUSKESMAS RASIMAH AHMAD DAN PUSKESMAS MANDIANGIN KOTA BUKITTINGGI - Widya Sari; Deswati Deswati; Khairil Armal (LPPM Universitas Mohammad Natsir Bukittinggi, 2026)
Tuberculosis (TB) is a global health problem requiring patient adherence to treatment. This study aimed to evaluate the effect of pharmacist-led medication counseling on tuberculosis medication adherence in patients at Puskesmas Rasimah Ahmad and Puskesmas Mandiangin, Bukittinggi City. The research employed a quasi-experimental design with a pretest-posttest one-group approach. The sample comprised 24 TB patients selected through total sampling. Data were collected using the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire before and after the counseling intervention. Data analysis included univariate and bivariate analyses using Kendall's tau-b, Wilcoxon signed-rank test, and Mann-Whitney U test. The findings indicated no association between age and TB treatment adherence before and after counseling. However, there was an association between gender, education, and occupation with TB treatment adherence after counseling. Treatment duration also showed a significant influence on patient adherence. Patient adherence levels increased significantly after counseling in both health centers (Puskesmas Rasimah Ahmad: p=0.024; Puskesmas Mandiangin: p=0.034). No significant difference in adherence levels was found between the two health centers post-counseling (p=0.320). This study concludes that pharmacist-led medication counseling effectively improves TB patient adherence. Healthcare professionals, particularly pharmacists, are encouraged to provide interactive and repetitive counseling to TB patients to support treatment success.